Paradigmatic status of an endo- and exoglucanase and its effect on crystalline cellulose degradation - Moraïs Sarah; Barak Yoav; Lamed Raphael; Wilson David B; Xu Qi; Himmel Michael E; Bayer Edward A (Biotechnology for Biofuels, 2012)
Abstract Background Microorganisms employ a multiplicity of enzymes to efficiently degrade the composite structure of plant cell wall cellulosic polysaccharides. These remarkable enzyme systems include glycoside hydrolases (cellulases, hemicellulases), polysaccharide lyases, and the carbohydrate esterases. To accomplish this challenging task, several strategies are commonly observed either separately or in combination. These include free enzyme systems, multifunctional enzymes, and multi-enzyme self-assembled designer cellulosome complexes. Results In order to compare these different paradigms, we employed a synthetic biology approach to convert two different cellulases from the free enzymatic system of the well-studied bacterium, Thermobifida fusca, into bifunctional enzymes with different modular architectures. We then examined their performance compared to those of the combined parental free-enzyme and equivalent designer-cellulosome systems. The results showed that the cellulolytic activity displayed by the different architectures of the bifunctional enzymes was somewhat inferior to that of the wild-type free enzyme system. Conclusions The activity exhibited by the designer cellulosome system was equal or superior to that of the free system, presumably reflecting the combined proximity of the enzymes and high flexibility of the designer cellulosome components, thus enabling efficient enzymatic activity of the catalytic modules.